Collaborative Learning, the Use of NICTs and Interaction among Science Teachers: Necessary Skills and Problems - Manuel Juárez Pacheco; Guillermina Waldegg Casanova (Universidad Autónoma de Baja California, 2005)
This study analyzes the practices of a group of high school science teachers in the development of a training seminar using the Computer-supported Collaborative Learning (CSCL) approach. The pedagogical model, the tools used in collaboration, and the development of group dynamics are all described. The analysis is carried out using categories based on the concept of social infrastructure, which permits the identification of some of the skills required as well as problems that arose during the teachers' synchronous and asynchronous interactions.